2008
DOI: 10.1089/dia.2008.0244
|View full text |Cite
|
Sign up to set email alerts
|

The IRIS V Study: Pioglitazone Improves Systemic Chronic Inflammation in Patients with Type 2 Diabetes Under Daily Routine Conditions

Abstract: These observational results, obtained from a nonselected patient population under daily routine conditions, confirm the benefits of pioglitazone treatment on blood glucose, lipid metabolism, and blood pressure. The results show that pioglitazone treatment improves chronic vascular inflammation, which may be associated with reduced cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
3
13
1
3
Order By: Relevance
“…Based on these observations, it can be speculated that the reduction in major cardiovascular events reported in the PROspective pioglitAzone Clinical Trial In macroVascular Events (PROactive) study [30] and confirmed by meta-analyses, including all available pioglitazone trials [31][32], is partly due to some extraglycemic action of the drug. risk has been reported [33]. In the present study, the authors were able to show that in diabetic patients at low risk for cardiovascular disease, this beneficial (CRP-lowering) effect was superior to that achieved with metformin.…”
Section: Discussionsupporting
confidence: 55%
“…Based on these observations, it can be speculated that the reduction in major cardiovascular events reported in the PROspective pioglitAzone Clinical Trial In macroVascular Events (PROactive) study [30] and confirmed by meta-analyses, including all available pioglitazone trials [31][32], is partly due to some extraglycemic action of the drug. risk has been reported [33]. In the present study, the authors were able to show that in diabetic patients at low risk for cardiovascular disease, this beneficial (CRP-lowering) effect was superior to that achieved with metformin.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, studies have demonstrated that pioglitazone therapy benefits individuals with elevated hs-CRP values. [46][47][48][49][50][51][52][53] 54 published data of 136 Japanese type 2 diabetes patients showing that pioglitazone treatment (30 mg daily for 3 months) significantly reduced hyperglycemia and hs-CRP relative to an untreated control group. In fact, a stratification into glycemic control responders [>1% of reduction in hemoglobin A1c (HbA1c)] and nonresponders revealed that CRP reduction with pioglitazone occurred independently of changes in parameters related to glucose metabolism.…”
Section: Effects Of Pioglitazone Treatment On Hs-crp Reductionmentioning
confidence: 99%
“…After 20 weeks, hs-CRP levels had decreased significantly with pioglitazone therapy (baseline 3.3 ± 1.0 mg/liter vs end point 2.8 ± 2.3 mg/liter, p < 0.01). 50 The PIOglim study was a double-blind, parallel prospective study with 82 patients with type 2 diabetes mellitus treated previously with sulfonylurea monotherapy with insufficient glycemic control (HbA1c >7.0%). They were randomized either to uptitration of glimepiride (4 to 6 mg; n = 37; 22 males, 15 females, age: 60 ± 9 years, HbA1c: 7.5 ± 0.6%, BMI: 31.6 ± 5.7 kg/m²) or to receive a glimeperide + pioglitazone combination (uptitration possible with 2 mg + 30 mg, 4 mg + 30 mg, and 4 mg +45 mg; 30/45 mg, n = 45; 25 males, 20 females, age: 62 ± 8 years, HbA1c: 7.2 ± 0.6%, BMI: 33.5 ± 6.2 kg/m²) for the next 6 months.…”
Section: Effects Of Pioglitazone Treatment On Hs-crp Reductionmentioning
confidence: 99%
“…РАППγ угнетает продукцию жировой тканью и макрофагами провоспалительных цитокинов: ФНО-а, ИЛ-6, резистина и других провоспалительных цитокинов [13]. ТЗД, как и фибраты, обладают проти-вовоспалительной активностью как на системном, так и на локальном уровнях [14].…”
Section: раппγunclassified